Influence of Zirconium on the Corrosion Passivation of Titanium in Simulated Body Fluid - Hamad F. Alharbi (MDPI AG, 2021)
Pure Ti and 85%Ti-15%Zr alloy were sintered in a heat induction high frequency furnace. The corrosion behaviour of Ti and 85%Ti-15%Zr in simulated body fluid (SBF) was studied. The work was achieved using different techniques as the cyclic polarization (PCP), the impedance spectroscopy (EIS), and the change of the potentiostatic current with time (PCT) experiments. The morphology of the surfaces of Ti and Ti-Zr after being corroded in SBF for 72 were investigated by a scanning electron microscope (SEM) and the analysis for the layer formed on that surface was collected via energy dispersive X-ray (EDX). Results depicted that the 15% Zr present within Ti decreases the corrosion via increasing Ti corrosion resistance and minimizing its measured corrosion rate. PCP data proved that the addition of Zr reduced all anodic, cathodic and corrosion currents. EIS results confirmed that Zr has a positive impact on the reduction of corrosion resistance. PCT, SEM, and EDX examinations displayed that both Ti and Ti-Zr alloy don’t show pitting corrosion even after 72 h exposure to SBF.